The Second Amendment and gun control: freedom, fear, and the American Constitution - Cornell, Saul (Controversies in American constitutional law, 2019)
Constitutional mythology and the future of Second Amendment jurisprudence after Heller / Saul Cornell -- The Second Amendment right to self-defence : the core freedom in the new century / Joyce Lee Malcolm -- Annie get your gun : women, performance, and the Western heroine / Karen Jones -- "A gun is a gun is anyone's hand" : shooting the gang girl in mi vida loca / Emma Horrex -- "The thought of a black male with a weapon scares America" : African Americans, the Second Amendment, and the racial politics of armed self-defense in the Civil Rights Era and beyond / Simon Wendt and Rebecca Rössling -- From virtuous armed citizen to "cramped little risk-fearing man" : the meaning of firearms in an insecure era / Kevin Yuill -- Gun rights and the rule of law / Firmin Debrabander -- To endure for all time or to change with the times? the Supreme Court and the Second Amendment / Emma Long -- Mr. Gingrich's bequest : globalising the Second Amendment? / Peter Squires -- The universal right of self-defense, and the auxiliary right to defensive arms / David B. Kopel